Order, Identity, and the “New Self”: Reading Ephesians Through Social Representations Theory - William B. Bowes (Religions)
Social representations theory (SRT) refers to an approach within social psychology focusing on systems of beliefs, concepts, and values that establish social order and allow for individuals and groups to identify and understand themselves vis-à-vis others. It involves the ascription of meaning to phenomena so that the unfamiliar is made familiar, and new concepts are integrated into existing worldviews in an ongoing process of constructing and interpreting social realities. This approach has not yet been applied to any biblical texts, and this article will explore how such an application would prove fruitful for understanding the processes of identification and community formation in early Christian groups, with a specific focus on Ephesians. This study will focus on how the concepts of reconciled differences (Eph 2.11–22) and of the “new self” (Eph 4.17–32) are communicated to the readers. Analyzing these concepts through SRT will elucidate how the author advocates for certain beliefs, concepts, and values as part of the community members’ process of aligning themselves with their newly created self. Reading Ephesians through SRT can better elucidate how the text reflects its enigmatic community, which was being formed and reformed through identification, division, and re-identification in the tumultuous second half of the first century.